Tanzania : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents the Joint Staff Assessment of Tanzania's Poverty Reduction Strategy Paper (PRSP) Progress Report. Despite a drought, real economic growth is estimated to have been about 5 percent, sound macroeconomic management was maintained, and notable progress was made in the areas of education and financial sector reform, among others. The report illustrates a number of emerging weaknesses in the Poverty Reduction Strategy process, pointing to areas for attention in the main update. Foremost among them are the need to link the technical-level reviews with a more policy-based debate on sector strategies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet